1997
DOI: 10.1056/nejm199708073370603
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Etidronate Therapy to Prevent Corticosteroid-Induced Osteoporosis

Abstract: Intermittent etidronate therapy prevents the loss of vertebral and trochanteric bone in corticosteroid-treated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
297
0
20

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 656 publications
(327 citation statements)
references
References 14 publications
10
297
0
20
Order By: Relevance
“…35 A randomized controlled study using 12 months of etidronate and calcium therapy reported prevention of bone loss and vertebral fractures in 141 patients receiving high-dose corticosteroids. 36 However, there are few studies in the post-OLT setting. A trial of calcitonin in the first 6 months after OLT was not useful in preventing post-OLT bone loss, 37 although a combination of calcitonin and biphosphonates for 12 months after OLT showed some improvement in BMD.…”
Section: Discussionmentioning
confidence: 99%
“…35 A randomized controlled study using 12 months of etidronate and calcium therapy reported prevention of bone loss and vertebral fractures in 141 patients receiving high-dose corticosteroids. 36 However, there are few studies in the post-OLT setting. A trial of calcitonin in the first 6 months after OLT was not useful in preventing post-OLT bone loss, 37 although a combination of calcitonin and biphosphonates for 12 months after OLT showed some improvement in BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, even small doses of administered cyclical hormones resulted in exacerbation of the patient's premenstrual asthma. The osteopenia of oestrogen deficiency can be treated with bisphosphonates [6]. An alternative strategy would be the use of continuous HRT preparations in order to avoid hormonal fluctuations but this has yet to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…In another study in post-menopausal women, the cyclic administration of etidronate in combination with the vitamin D metabolite ergocalciferol increased lumbar spine and femoral neck BMD by 7 and 2.5% respectively, in the first year of GC therapy, while in the second year BMD continued to increase at the femoral neck and remained stable at lumbar spine [29]. Furthermore, in a randomized placebo-controlled trial, 141 men and women recently started on GC therapy were treated for 1 year with either etidronate (400 mg/day) or placebo for 14 days, followed by calcium (500 mg/day) for 76 days: with etidronate bone density increased significantly at lumbar spine and trochanter, but not at the femoral neck [1]. Similar results were reported in another study with 117 patients followed over 1 year [119].…”
Section: Calcium Vitamin D and Thiazide Diureticsmentioning
confidence: 99%
“…In a recently published study over 5 years, including 352 patients who had been taking GCs for at least 1 year for the treatment of asthma, cyclical etidronate caused a significant increase in lumbar spine BMD [16]. Although the results on BMD were consistent across studies, reduction of fracture risk could not be established with etidronate [1,16].…”
Section: Calcium Vitamin D and Thiazide Diureticsmentioning
confidence: 99%